Assessing Role of Major Drivers in Recent Decline of Monarch Butterfly Population in North America - Belsky, Joseph; Joshi, Neelendra K. (Frontiers in Environmental Science, 2018)
Monarch (Danaus plexippus L.) is a long distance migratory species of butterfly in North America that has experienced population declines in recent years. Several interacting factors have been postulated to contribute to this decline. For example, reduced overwintering habitat in Mexico as a result of logging leading to deforestation and reduced breeding habitats in the United States. Decreased spring breeding populations and inclement weather patterns have also been proposed. Herbicides are commonly used in many agricultural production systems planted with genetically modified (GM) cultivars that are resistant to these chemicals. However, the non-target effects of these commonly used herbicides to the monarch host-plant, milkweed (Asclepias spp. L.), which commonly grows within GM planted agricultural fields has also been hypothesized to explain reduced breeding habitats in the Midwestern United States. Currently, significant uncertainty regarding the dynamics of these multiple hypotheses and how their interaction may impact the eastern monarch butterfly population remains. Meanwhile, several efforts to help monarchs have been launched; for example, milkweed plantings and campaigns to minimize deforestation in overwintering habitats. In this context, this mini-review highlights different population decline hypotheses and conservation initiatives and discusses knowledge gaps in awareness and research efforts to mitigate the eastern monarch butterfly population decline.